PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. ASTRA MOTOR CABANG BENGKULU - Melda Yunita; Fedi Faizar Pratama (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2022)
This study aims to determine the effect of compensation, work discipline, and motivation on the performance of employees of PT. Astra Honda Panorama Bengkulu City either partially or simultaneously. There are several independent variables (x) that will be discussed in this study, including Compensation, Work Discipline, and Motivation. The object of this research is the employees of PT. Astra Honda Panorama Bengkulu City, totaling 40 people. In this research, the author uses data collection methods by means of observation, distributing questionnaires or questionnaires and interviews.In this study, there are several data analysis techniques used, including using instrument tests, classical assumption tests, analysis of respondents' responses, multiple linear regression analysis, determinant coefficients, and also hypothesis testing. From the results of multiple linear regression, the regression equation is as follows: Y = 4.287 + 0.653 (X1) + 0.159 (X2) + 0.167 (X3). The results of the t test on the Compensation variable (X1), show t count > t table, namely (4.083 > 2.02809) and sig < a (0.000 < 0.050). Discipline (X2), shows t arithmetic > t table, namely (2.404 > 2.02809) and sig < a (0.017 < 0.050). Motivation (X3), shows t arithmetic > t table, namely (2.344 > 2.02809) and sig < a (0.033 < 0.050). From the results of the tests that have been carried out, it can be concluded that the variables of Compensation, Work Discipline, and Motivation have a partial or simultaneous effect on the performance of employees of PT. Astra Honda Panorama Bengkulu City.Â Keywords : Compensation, Work Discipline, Employee Motivation and Performance